2004
DOI: 10.1200/jco.2004.03.098
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Cardiac Follow-Up in Relapse-Free Patients After Six Courses of Fluorouracil, Epirubicin, and Cyclophosphamide, With Either 50 or 100 mg of Epirubicin, As Adjuvant Therapy for Node-Positive Breast Cancer: French Adjuvant Study Group

Abstract: PURPOSE To evaluate long-term cardiac function in patients without disease who had received six cycles of fluorouracil 500 mg/m(2), epirubicin 50 mg/m(2), and cyclophosphamide 500 mg/m(2) (FEC 50) or the same regimen with epirubicin 100 mg/m(2) (FEC 100) as adjuvant chemotherapy for node-positive breast cancer in the French Adjuvant Study Group-05 trial. PATIENTS AND METHODS One hundred fifty patients (FEC 50, n = 65; FEC 100, n = 85) who were without disease and who gave their informed consent were enrolled f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(41 citation statements)
references
References 27 publications
0
38
0
3
Order By: Relevance
“…A 7-year follow-up meta-analysis of 3,577 patients in the FASG trials found that the risk for developing left ventricular dysfunction was 1.36% (95% CI, 1.10%-1.62%) in a total of 2,553 patients who received cumulative doses of epirubicin ranging from 300 mg/m 2 to 628 mg/m 2 , compared with 0.2% (95% CI, 0.06% -0.36%) in patients on other regimens (p = .004) [41]. A long-term (>10 years) prospective follow-up study (FASG 05) assessed cardiac function in 150 disease-free patients; 65 had received cumulative doses of epirubicin of 300 mg/ m 2 (FEC50), and 85 had received epirubicin doses of 600 mg/m 2 (FEC100) [46]. Two patients receiving FEC100 experienced CHF that was possibly related to epirubicin, while a total of 18 FEC100 patients developed asymptomatic left ventricular dysfunction that was possibly or probably related to the treatment.…”
Section: Epirubicin's Safety Profilementioning
confidence: 99%
See 1 more Smart Citation
“…A 7-year follow-up meta-analysis of 3,577 patients in the FASG trials found that the risk for developing left ventricular dysfunction was 1.36% (95% CI, 1.10%-1.62%) in a total of 2,553 patients who received cumulative doses of epirubicin ranging from 300 mg/m 2 to 628 mg/m 2 , compared with 0.2% (95% CI, 0.06% -0.36%) in patients on other regimens (p = .004) [41]. A long-term (>10 years) prospective follow-up study (FASG 05) assessed cardiac function in 150 disease-free patients; 65 had received cumulative doses of epirubicin of 300 mg/ m 2 (FEC50), and 85 had received epirubicin doses of 600 mg/m 2 (FEC100) [46]. Two patients receiving FEC100 experienced CHF that was possibly related to epirubicin, while a total of 18 FEC100 patients developed asymptomatic left ventricular dysfunction that was possibly or probably related to the treatment.…”
Section: Epirubicin's Safety Profilementioning
confidence: 99%
“…Of the 18 patients who developed asymptomatic left ventricular cardiac dysfunction, all had received left chest wall and nodal irradiation. Thus, the combination of FEC and postoperative irradiation resulted in an acceptable incidence of cardiac dysfunction [46]. It should be noted, however, that at equimolar doses, epirubicin and doxorubicin result in the same response rates and 1-year survival rates, as well as OS rates, in patients with metastatic breast cancer [47].…”
Section: Epirubicin's Safety Profilementioning
confidence: 99%
“…Nevertheless, cardiotoxicity induced by anthracyclin may cause long term side effects after treatment, hence, it has been considered to be an important problem (1,2). In other words, in cases of malilignant lymphoma, acute leukemia, multiple myeloma and other hematological tumors or breast cancer among solid tumors that could be completely cured or long term survival is possible by the treatment with chemotherapy including anthracyclin, but heart failure developed during treatment or after treatment is a severe side effect that threatens the life of patients and deteriorates quality of life (3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between cumulative anthracycline dose and long-term cardiac effects has been evaluated in several studies, with a reported rate of congestive heart failure in the range of 0%-2%, with a median follow-up time of 39 -74 months [23][24][25][26][27][28]. Recently, a study reported on long-term cardiac outcome in patients treated with dose-dense and doseintense sequential doxorubicin, paclitaxel, and cyclophosphamide in the adjuvant setting, wherein doxorubicin was given at 90 mg/m 2 every 14 days for three cycles, and no cardiac-related deaths were seen [29].…”
Section: Discussionmentioning
confidence: 99%